Desain Rancang Bangun Dapur Umum Portable dalam Penanggulangan Bencana Alam - Hidayanto, Andi Farid; Rulia, Anna - (PANGGUNG, 2016)
ABSTRACTÃÂ Indonesia is a disaster-prone areas. To meet the logistical ÃÂ needs of the victim ÃÂ and the officer needed a common kitchen. Common kitchen that is generally in the form of tents, buildings used as shelters, or modified car. Common kitchen there is an emergency nature, ÃÂ improvise, and how far from the disaster site. These problems need to design a common kitchen for natural disaster management, ÃÂ which can meet the needs, the officer and the victim. In designing ÃÂ methods Pahl and Beitz with steps Planning and explanation ÃÂ of the task, ÃÂ design concept, ÃÂ design forms, and design details. Collecting ÃÂ data using methods Individual ÃÂ Questionnaire ÃÂ and Focus Group Dis- cussion the results obtained attributes ÃÂ required in the design. Results of the research is a com- mon kitchen design for a natural disaster ÃÂ are portable, easily assembled and disassembled, can be setÃÂ  up in various ÃÂ locations ÃÂ condition, ÃÂ easy to operate, able to accommodate facilities ÃÂ and needs. Common ÃÂ kitchen ÃÂ design ÃÂ produced in the form ÃÂ of large-scale ÃÂ three-dimensionalÃÂ  ÃÂ model, a blueprint ÃÂ for the technical ÃÂ specifications, ÃÂ and the protoype.ÃÂ Keywords: natural disasters; ÃÂ design; soup kitchen;ÃÂ  portable.ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Indonesia merupakan daerah rawan bencana. Memenuhi kebutuhan logistik korban dan petugas diperlukan dapur umum. Dapur umum yang ada umumnya berupa tenda peleton, bangunan yang dijadikan posko, atau mobil yang dimodifikasi. Dapur umum yang ada sifatnya darurat, seadanya dan lokasinya jauh dari lokasi bencana. Dari masalah tersebut perlu desain dapur umum untuk penanggulangan bencana alam, yang bisa memenuhi kebutuhan, baik petugas maupun korban. Dalam mendesain menggunakan metode Pahl dan Beitz dengan langkah-langkah Perencanaan dan penjelasan tugas, Perancangan konsep, Perancangan bentuk, dan Perancangan detail. Pengumpulan data menggunakan metode Individual Questionnaire dan Focus Group Discussion yang hasilnya didapatkan atribut yang diperlukan dalam desain. Hasil dari penelitian berupa desain dapur umum untuk penanggulangan bencana alam yang portable, mudah dirakit dan dibongkar, dan dapat didirikan di lokasi yang beraneka kondisi, mudah dioperasikan, mampu menampung fasilitas dan kebutuhan. Desain dapur umum yang dihasilkan dalam bentuk model tiga dimensi berskala, blue print spesifikasi teknis, dan protoype.ÃÂ Kata kunci: bencana alam, desain, dapur umum, portable.